Redox chemistry of CeO2 nanoparticles in aquatic systems containing Cr(vi)(aq) and Fe2+ ions. Issue 7 (21st June 2019) - Ray, Jessica R.; Wu, Xuanhao; Neil, Chelsea W.; Jung, Haesung; Li, Zhichao; Jun, Young-Shin
Abstract : CeO2 nanoparticles are extensively used in industrial applications owing to their high redox-catalytic activities and, as a result, may appear in aquatic environments where they undergo significant surface chemistry transformation with other redox-active species. Abstract : CeO2 nanoparticles (NPs) are extensively used in industrial applications owing to their high redox-catalytic activities and, as a result, may appear in aquatic environments where other redox-active species may coexist. To better predict the fate and transport of these nanomaterials, a comprehensive, mechanistic understanding of the physicochemical behaviors and transformation of CeO2 NPs in complex, redox-active aqueous systems is needed. In this study, we investigated redox reactions of CeO2 NPs with Fe 2+ and Cr(vi ) ( i.e., model redox-sensitive species) at pH 5. We found that the coexistence of 0.1 mM Fe 2+ and 1 (or 5) μM Cr(vi )(aq) promoted formation of Fe(iii ) (hydr)oxides and increased CeO2 NP colloidal stability. Specifically, without Cr(vi ), Ce 3+ (aq) was rapidly released from the CeO2 /Fe 2+ redox reaction, while the subsequent oxidation of Fe 2+ to Fe 3+ and formation of Fe(iii ) (hydr)oxides was slow. However, when Fe 2+ and Cr(vi ) coexist with CeO2 NPs, the dissolution of CeO2 NPs was slower than without Cr(vi ), and Fe(iii ) (hydr)oxide precipitation on and near CeO2 NPs significantly increased. The fast formation of Fe(iii ) (hydr)oxides can be attributed to facilitated Fe 3+ hydrolysis by Cr(vi )(aq). Consequently, these new hybrid Fe(iii )–CeO2 NPs ( i.e., CeO2 NPs coated with Fe(iii ) solid phases) formed during redox-induced surface transformations exhibited a higher hydrophilicity, a more positive surface charge, and a greater colloidal stability compared to CeO2 NPs in systems without Cr(vi ). These findings reveal unexplored changes in surface chemistry and mobility of CeO2 nanomaterials in complex redox-active aqueous systems.